Economic evaluations of personalized medicine: existing challenges and current developments - Shabaruddin FH; Fleeman ND; Payne K (Dove Medical Press, 2015)
Fatiha H Shabaruddin,1 Nigel D Fleeman,2 Katherine Payne3 1Department of Pharmacy, University of Malaya, Kuala Lumpur, Malaysia; 2Liverpool Reviews and Implementation Group (LRiG), University of Liverpool, Liverpool, UK; 3Institute of Population Health, The University of Manchester, Manchester, UK Abstract: Personalized medicine, with the aim of safely, effectively, and cost-effectively targeting treatment to a prespecified patient population, has always been a long-time goal within health care. It is often argued that personalizing treatment will inevitably improve clinical outcomes for patients and help achieve more effective use of health care resources. Demand is increasing for demonstrable evidence of clinical and cost-effectiveness to support the use of personalized medicine in health care. This paper begins with an overview of the existing challenges in conducting economic evaluations of genetics- and genomics-targeted technologies, as an example of personalized medicine. Our paper illustrates the complexity of the challenges faced by these technologies by highlighting the variations in the issues faced by diagnostic tests for somatic variations, generally referring to genetic variation in a tumor, and germline variations, generally referring to inherited genetic variation in enzymes involved in drug metabolic pathways. These tests are typically aimed at stratifying patient populations into subgroups on the basis of clinical effectiveness (response) or safety (avoidance of adverse events). The paper summarizes the data requirements for economic evaluations of genetics and genomics-based technologies while outlining that the main challenges relating to data requirements revolve around the availability and quality of existing data. We conclude by discussing current developments aimed to address the challenges of assessing the cost-effectiveness of genetics and genomics-based technologies, which revolve around two central issues that are interlinked: the need to adapt available evaluation methods and identifying who is responsible for generating evidence for these technologies. Keywords: pharmacogenetics, pharmacogenomics, cost-effectiveness, economic evaluation, somatic variations, germline variations